2019
DOI: 10.1186/s12903-019-0937-8
|View full text |Cite
|
Sign up to set email alerts
|

The application of virtual reality and augmented reality in Oral & Maxillofacial Surgery

Abstract: Background: Virtual reality is the science of creating a virtual environment for the assessment of various anatomical regions of the body for the diagnosis, planning and surgical training. Augmented reality is the superimposition of a 3D real environment specific to individual patient onto the surgical filed using semi-transparent glasses to augment the virtual scene.. The aim of this study is to provide an over view of the literature on the application of virtual and augmented reality in oral & maxillofacial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
146
0
14

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(162 citation statements)
references
References 42 publications
2
146
0
14
Order By: Relevance
“…This allows pre interaction between the dental practitioner and the auxiliary staff, such as a dental technician to prospectively design, and thus decide the best options for a patient’s prosthesis, for example in the construction of dentures utilizing AR/VR systems [ 9 ]. On the other hand, oral maxillofacial surgeons, with the aid of specialized software and an engineering team are able to predesign a surgical template or plan based on the current disease manifestation and condition, for example in complex trauma and implant cases ( Figure 2 ) [ 10 ]. This allows a more precise surgical technique to be implemented as it reduces the risk of human error in the surgical field as it provides a quicker surgical recovery turnaround, hence, reducing potential unnecessary contamination of the surgical site and surgical morbidity [ 11 , 12 ].…”
Section: Augmented and Virtual Realitymentioning
confidence: 99%
“…This allows pre interaction between the dental practitioner and the auxiliary staff, such as a dental technician to prospectively design, and thus decide the best options for a patient’s prosthesis, for example in the construction of dentures utilizing AR/VR systems [ 9 ]. On the other hand, oral maxillofacial surgeons, with the aid of specialized software and an engineering team are able to predesign a surgical template or plan based on the current disease manifestation and condition, for example in complex trauma and implant cases ( Figure 2 ) [ 10 ]. This allows a more precise surgical technique to be implemented as it reduces the risk of human error in the surgical field as it provides a quicker surgical recovery turnaround, hence, reducing potential unnecessary contamination of the surgical site and surgical morbidity [ 11 , 12 ].…”
Section: Augmented and Virtual Realitymentioning
confidence: 99%
“…However, the complexity of the surgical procedure requires sufficient training of the surgeon and team, and a learning curve for the procedure must be observed [ 24 ]. Further development of implant surgical procedures based on technologies of virtual reality and augmented reality is rewarded with an increase in the quality of care [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study also reported the use of 3D files based on real patient situation to teach dental surgery [27]. Moreover, these files can be easily integrated into preclinical simulation using haptic or virtual reality simulators, which is regarded with interest in dental education [7,28,29]. Figure 6.…”
Section: Discussionmentioning
confidence: 99%